Gender Representation in Postcolonial African Literature - Bizimungu, Ian (American Journal of Literature Studies, 2024)
Purpose: The aim of the study was to assess the gender representation in postcolonial African literature. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that authors often critique patriarchal structures and colonial legacies that have influenced gender dynamics. Female characters in these narratives are depicted as resilient and multifaceted, challenging traditional roles and seeking empowerment. Works by writers such as Chimamanda Ngozi Adichie and Tsitsi Dangarembga highlight the struggles and triumphs of women navigating postcolonial societies, reflecting broader themes of identity, autonomy, and resistance. Additionally, postcolonial African literature often explores the intersectionality of gender with race, class, and ethnicity, offering a nuanced understanding of the lived experiences of African women and men in a rapidly changing world. Implications to Theory, Practice and Policy: Postcolonial theory, feminist literary theory and queer theory may be used to anchor future studies on assessing the gender representation in postcolonial African literature. Supporting emerging authors through literary grants and mentorship programs is essential for promoting diversity and inclusivity in literary production. Promoting gender-inclusive literary awards can incentivize authors to explore and challenge traditional gender norms in their works.